The story of time - Lippincott, Kristen; National Maritime Museum (Great Britain) (London : Merrell Holberton in association with National Maritime Museum, 1999)
"The Story of Time is a unique multi-disciplinary, cross-cultural exploration of every aspect of time across the Earth, from the earliest civilizations to the beginning of the third millennium. With original contributions from an outstanding cast of international authors, it questions people's perceptions of time and reflects the many ways in which cultures around the world have responded to time, measured time and expressed their understanding of time." "The Story of Time serves as an exceptionally stimulating and informative guide to all who wish to travel through the most universal yet mysterious of subjects. The book is published to coincide with a major exhibition being held at the Queen's House of the National Maritime Museum in Greenwich and with the celebration of the new millennium at the Royal Observatory, the home of Greenwich Mean Time and the Prime Meridian of the World and the point at which the new millennium begins." -- Book jacket.
The creation of time. -- The measurement of time. -- The depiction of time. -- The experience of time. -- The end of time.
Published to coincide with an exhibition held at the National Maritme Museum in Greenwich and with the celebration of the new millennium at the Royal Observatory.
Bibliography: p.300-301.
Keywords: Time -- Exhibitions